2000
DOI: 10.1007/s004280050469
|View full text |Cite
|
Sign up to set email alerts
|

Mammographically detected in situ lobular carcinomas of the breast

Abstract: We present ten cases of mammographically detected lobular carcinoma in situ (LCIS), involving a single area of variable size (up to a quadrant) in seven cases and the entire gland in three cases. Histologically, calcifications were associated with necrotic central areas within the in situ carcinomatous foci. Multiple foci of LCIS were observed in all five cases in which mastectomy had been performed. Cytologically, the lesions were characterized by a solid proliferation of round noncohesive cells with nuclei o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 12 publications
(18 reference statements)
3
37
1
Order By: Relevance
“…21 Furthermore, lobular carcinoma in situ with necrosis can be associated with microcalcifications and can present mammographically like comedo-type ductal carcinoma in situ. 1,8 In contrast to many previous studies on lobular neoplasia, our study does not support routine excision for classic lobular carcinoma in situ or atypical lobular hyperplasia, but does support routine excision for nonclassic lobular carcinoma in situ, including pleomorphic lobular carcinoma in situ and lobular carcinoma in situ with necrosis. Concordance of radiology and pathology findings must be considered when making a decision to recommend excision.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…21 Furthermore, lobular carcinoma in situ with necrosis can be associated with microcalcifications and can present mammographically like comedo-type ductal carcinoma in situ. 1,8 In contrast to many previous studies on lobular neoplasia, our study does not support routine excision for classic lobular carcinoma in situ or atypical lobular hyperplasia, but does support routine excision for nonclassic lobular carcinoma in situ, including pleomorphic lobular carcinoma in situ and lobular carcinoma in situ with necrosis. Concordance of radiology and pathology findings must be considered when making a decision to recommend excision.…”
Section: Discussioncontrasting
confidence: 99%
“…6 Rosen described 'florid' lobular carcinoma in situ characterized by 'tumor cells that fill and expand the duct lumen' that 'may develop central necrosis and calcifications'. 7 Sapino et al 8 and Fadare et al 9 also have defined in situ lesions with morphologic features of lobular neoplasia but with necrosis as lobular carcinoma in situ. Not only do both pleomorphic lobular carcinoma in situ and lobular carcinoma in situ with necrosis show different morphology, they can also exhibit a more aggressive biologic marker profile compared to classic lobular carcinoma in situ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,[19][20][21][22] They are clinically occult, and although they are often also mammographically silent, a significant minority of lobular neoplasia cases diagnosed on core biopsy have associated microcalcifications. [23][24][25][26] Data derived from the Surveillance, Epidemiology and End Results Program 27 have shown that the ageadjusted, age-specific rates of LCIS among women in the United States has increased fourfold between the late 70s (0.9 per 100 000 person years) and late 90s (3.2 per 100 000 person years). Women aged between 50 and 59 years experienced the greatest absolute increase in incidence from 1978 to 1998.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In ADH, the presence and role of p53 mutations is still an open field: p53 mutations were initially not documented (Chitemerere et al 1996); subsequently studies pointing to p53 mutations appeared (Kang et al 2001), and, more recently, the presence of mutated p53 in ADH has been demonstrated with the use of laser capture microdissection microscope, singlestranded conformational polymorphism (SSCP) and sequencing (Keohavong et al 2004). Regarding LN, there is scarcity of data: in two studies, no p53 immunoreactivity was demonstrated in LN lesions (Siziopikou et al 1996;Sapino et al 2000), whereas a more recent study on LCIS reported p53 immunoreactivity in one fifth of cases (Mohson et al 2005).…”
Section: P53mentioning
confidence: 99%